2021
DOI: 10.3390/rs13020234
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Downscaling Scheme for High-Resolution Precipitation Estimates over a High Mountainous Watershed

Abstract: Satellites are capable of observing precipitation over large areas and are particularly suitable for estimating precipitation in high mountains and poorly gauged regions. However, the coarse resolution and relatively low accuracy of satellites limit their applications. In this study, a downscaling scheme was developed to obtain precipitation estimates with high resolution and high accuracy in the Heihe watershed. Shannon’s entropy, together with a semi-variogram, was applied to establish the optimal precipitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…However, some studies reported opposite results, indicating an improvement in precipitation data after residual correction. Zhao [69] illustrated that residual correction played an important role in RF-based downscaling. Residual correction greatly increased the accuracy of the precipitation estimation conducted by artificial neural networks [33].…”
Section: Performance Of Downscaling Results After Gda Calibration And...mentioning
confidence: 99%
“…However, some studies reported opposite results, indicating an improvement in precipitation data after residual correction. Zhao [69] illustrated that residual correction played an important role in RF-based downscaling. Residual correction greatly increased the accuracy of the precipitation estimation conducted by artificial neural networks [33].…”
Section: Performance Of Downscaling Results After Gda Calibration And...mentioning
confidence: 99%
“…However, careful optimization of the hyperparameters is necessary to achieve the best results. With the right approach, XGBoost enables data scientists to build accurate and reliable models that offer valuable insights into complex datasets 43 . XGBoost algorithm can be written aswhere f k is the leaf node's regular term of the kth classification tree, l y i , y i is the training error of sample xi, and Obj is the objective function 44 .…”
Section: Xgboost (Xgb)mentioning
confidence: 99%
“…Multisource high-performance satellite precipitation products along with geographical auxiliary data have also shown effective role to improve precipitation estimations in many researches Jia et al, 2011;Khan & Bhuiyan, 2021;Nosratpour et al, 2022;Retalis et al, 2017;Zhao, 2021). Retalis et al (2017) enhanced the Climate Hazards Group InfraRed Precipitation with Station data (CHIRPS) retrievals for the years 1999-2010 by using altitude and NDVI in conjunction with an artificial neural network (ANN) model.…”
Section: Introductionmentioning
confidence: 99%